Steroid-resistant minimal change disease and hypothyroidism: Case report - Zambrano-Urbano, José Leonel; López-Delgado, Darío Sebastián; Delgado-Truque, Andrés Emilson; Casanova, María Eugenia (Universidad y Salud, 2021)
Introduction: Minimal change disease is a rare cause of nephrotic syndrome in adults, and its association with hypothyroidism is even more exceptional. This renal pathology is considered to respond favorably to glucocorticoid management and has a low resistance frequency. How to approach this disease is currently under investigation. Objective: To describe a rare etiology of adult nephrotic syndrome with unusual presentation, treatment, and outcome. Case presentation: A 53 years-old female patient who initially experienced nephrotic syndrome due to steroid-resistant minimal change disease, which was also associated with uncontrolled hypothyroidism. She required management with rituximab and control of the associated endocrinological disease, which was considered as the underlying disease. Conclusions: This clinical case shows (i) how the two aforementioned diseases can coexist and (ii) that a joint treatment is necessary. Establishing new therapies may be beneficial for adult populations, such as the benefits seen in this case with the use of rituximab. However, further studies are needed to strongly validate the effectiveness of the different treatments for these types of patients.